Removal of Lead and Zinc From Contaminated Soil by a Novel Chelating Surfactant. Issue 9 (8th June 2016) - Qiao, Hong‐tao; Zhao, Bao‐wei; Diao, Jing‐ru; Huang, Li‐ping; Zhong, Jin‐kui; Ma, Feng‐feng
Abstract : In the present study, the focus was to explore the feasibility of using a chelating surfactant, sodium N‐lauroyl ethylenediamine triacetate (LED3A), as an effective washing reagent for lead (Pb)‐ and zinc (Zn)‐contaminated soils. The total content of Pb and Zn was equal to 949.6 and 936.4 mg kg −1, respectively. A series of batch washing experiments was conducted. The results showed that the washing experiments reached equilibrium within 17 h, at >3 g L −1 LED3A. The desorption processes of Pb and Zn could be best described by the pseudo‐second‐order equation. The intra‐particle diffusion model implied that the desorption processes included three continuous stages, and that intra‐particle diffusion was not the only rate‐limiting step. Results from the effect of the LED3A concentration and temperature indicated that desorption of Pb and Zn was an endothermic process, and the optimum concentration of LED3A was 7 g L −1 . Data from sequential extractions showed that LED3A washing resulted in the decrease of the Pb and Zn percentage in the mobile fractions, and an increase in fractions strongly bonded to the soil matrix. LED3A showed a significant potential for chelating extensive amounts of the used heavy metals from contaminated soil. Abstract : A novel biodegradable chelating surfactant, sodium N‐lauroyl ethylenediamine triacetate (LED3A), has good surfactant performance with the ability to chelate heavy metal ions, forming stable chelate complexes. LED3A shows a significant potential for chelating extensive amounts of Pb and Zn from contaminated soil. After LED3A washing, Pb and Zn are relatively more difficulty released into the environment, and potentially less toxic.